Population genetic correlates of declining transmission in a human pathogen - Standwell C. Nkhoma; Shalini Nair; Salma Al‐Saai; Elizabeth Ashley; Rose McGready; Aung P. Phyo; François Nosten; Tim J. C. Anderson (Molecular Ecology, 2013)
Pathogen control programs provide a valuable, but rarely exploited, opportunity to directly examine the relationship between population decline and population genetics. We investigated the impact of an ~12‐fold decline in transmission on the population genetics of P lasmodium falciparum infections ( n = 1731) sampled from four clinics on the T hai– B urma border over 10 years and genotyped using 96 genome‐wide SNP s. The most striking associated genetic change was a reduction in the frequency of infections containing multiple parasite genotypes from 63% in 2001 to 14% in 2010 ( P = 3 × 10 −15 ). Two measures of the clonal composition of populations (genotypic richness and the β‐parameter of the Pareto distribution) declined over time as more people were infected by parasites with identical multilocus genotypes, consistent with increased selfing and a reduction in the rate at which multilocus genotypes are broken apart by recombination. We predicted that the reduction in transmission, multiple clone carriage and outbreeding would be mirrored by an increased influence of genetic drift. However, geographical differentiation and expected heterozygosity remained stable across the sampling period. Furthermore, N e estimates derived from allele frequencies fluctuation between years remained high (582 to ∞) and showed no downward trend. These results demonstrate how genetic data can compliment epidemiological assessments of infectious disease control programs. The temporal changes in a single declining population parallel to those seen in comparisons of parasite genetics in regions of differing endemicity, strongly supporting the notion that reduced opportunity for outbreeding is the key driver of these patterns.